APPEARANCE OF MAKSUD KARYIEV'S STYLE IN "IBN SINO" NOVEL - Mamurova Mushtari Makhammadjanovna (Journals Park Publishing, 2022)
This article analyzes some of the writer's unique styles in Maqsud Qariyev's novel "Ibn Sino".
Keywords: Ibn Sina; history; style